The cost of defection: the consequences of quitting Al-Shabaab - Taylor, Christian (International journal of conflict and violence, 2019)
This study investigates defections from the Al-Shabaab insurgency in Somalia. Thirty-two disengaged Al-Shabaab combatants were interviewed about their motivations, grievances, needs, and challenges in relation to the recruitment, defection, and post-defection phases. This paper focuses on post-defection challenges, where we found the primary concern to be lack of personal security. Without adequate security, disengaged combatants are vulnerable to being hunted and killed by Al-Shabaab. This significant threat discourages further mass and individual defections. We also found that disengaged combatants joined and defected out of religious zeal, to fight for what they believed to be a holy Islamic cause. This same zeal led them to defect, as they came to believe Al-Shabaab was not obeying the true Islamic faith. Indiscriminate killing by Al-Shabaab disenchants its religiously pious members, creating an opportunity to encourage mass and individual defections. However, if disengaged combatants are not protected from retribution,